Efeito de diferentes alimentos sobre a fecundidade de Amblyseius limonicus (Acarina: Phytoseiidae) - Noronha, Aloyséia Cristina da Silva; Mesa Cobo, Nora Cristina (1990)
This work was done at the International Center of Tropical Agriculture (CIAT), with the objective of checking the effect of differents food sources on the fertility of Amblyseius limonicus Garman & McGregor (Acarina: Phytoseiidae), predator of green mite (Mononychellus tanajoa) in cassava culture (Manihot esculenta Crantz), and to express the importance of food sources in mass production of integrated programs of pest control. In laboratory, at a temperature of 25 degrees C and at relative humidity 70 more or less 5, daily observations were made of the numbers of eggs of A. limonicus feeding on: polle of the castor oil plant (Ricinus communis), pollen of flowers bought in a supermarket, cassava leaf exsudate, green mite (Mononychellus caribeanae) (Tetranychidae), mealybug eggs (Phenacoccus herreni) (Pseudococcidae), thrips (Frankliniella williamsi) (Thripidae) and Amblystira sp. (Hemiptera: Tingidae). The results showed that A. limonicus feeding on thrips had a significantly higher rate of oviposition than on the other foods. There was not observed oviposition on cassava leaf exudate and mealybug eggs.